Preparation method of Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material

Through the preparation of the Mg/Al co-doping modified layered structure, the capacity loss and rate performance problems of cobalt-free lithium-rich manganese-based positive electrode materials are solved, which significantly improves the electrochemical performance and cycle stability and extends the capacity attenuation time.

CN119263361APending Publication Date: 2025-01-07CHANGDE COSPOWERS NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411184861.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The layered cobalt-free lithium-manganese-based positive electrode material has problems such as irreversible loss of capacity for the first time, poor rate performance, and faster capacity attenuation.

Method used

Using the preparation method of Mg/Al co-doping modified layered cobalt-free lithium-manganese-based positive electrode material, the mixture of Li2CO3, Mn oxide, Ni oxide, Mg compound, and Al compound was obtained by mechanical ball milling, and drying and roasting. The powder was mixed uniformly and secondary calcined at high temperature to form a Mg/Al co-doped modified layered structure.

Benefits of technology

It improves the electrochemical performance of the positive electrode material, reduces the first irreversible capacity loss, enhances the cycle stability and rate performance, and extends the capacity attenuation time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263361A_ABST
    Figure CN119263361A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material, and belongs to the technical field of lithium ion batteries. The method comprises the following steps: adding excessive Li2CO3, Mn oxide, Ni oxide, Mg compound and Al compound into a ball milling tank of an organic solvent, and fully mixing through mechanical ball milling to obtain uniform mixed powder; drying the mixed powder at 80 DEG C for 3-10 hours; the second-stage roasting temperature is 700-900 DEG C, the second-stage roasting time is 10-20 hours, and the Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material is obtained. The preparation method comprises the following steps: uniformly mixing the dried powder again, roasting at the room temperature to 350-500 DEG C, preserving heat for 3-6 hours, and roasting at the second-stage roasting temperature of 700-900 DEG C for 10-20 hours. The Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid-phase method is subjected to morphology analysis, and it is observed that sample particles are uniform in distribution and appropriate in particle size, which indicates that the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material possibly has good electrochemical performance. Al < 3 + > doping can effectively improve the electrochemical performance of the cobalt-free lithium-rich manganese-based positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-ion batteries, and in particular relates to a method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material. Background Art

[0002] As the global population grows rapidly, energy demand continues to rise. The large-scale exploitation and use of traditional fossil fuels such as coal, oil and natural gas have triggered serious energy crises and ecological environmental deterioration. The global climate is deeply affected by the continuous emission of greenhouse gases, which poses a serious threat to the development of human society. Electrochemical energy storage and conversion devices can play a vital role in the production and storage of energy due to their high efficiency and pollution-free operation. At present, lithium-ion battery (LIB) system, as a kind of energy storage device, occupies an important position in the field of renewable energy due to its huge potential. In lithium-ion batteries, the positive electrode material has always been considered the most core part, and it is also the key to improving battery performance and reducing costs.

[0003] Among the common positive electrode materials currently, high-nickel ternary materials have higher technical maturity and energy density, but due to their high Ni content, they will lead to Li / Ni mixing, and the cycle and safety performance needs to be improved. Lithium iron phosphate materials have high cycle stability and safety, but their energy density and tap density are relatively low. At the same time, due to the low ionic and electronic conductivity, the rate performance is not ideal. Considering the growing application requirements and concerns about toxicity and economy, manganese-based oxide positive electrode materials with Mn as the main transition metal element have aroused strong interest. Among them, the layered lithium-rich manganese-based positive electrode material xLi2MnO3·(1-x)LiMO2 (M=Mn, Ni, Co and other transition metal elements) can provide>250mAhg -1 It has the advantages of high specific capacity, good thermal stability and low cost.

[0004] In the world of lithium-rich cathode materials for batteries, cobalt plays a core role. It is essential for stabilizing the material structure and improving the overall performance of the battery. However, as a precious and non-renewable resource, cobalt has very limited reserves. With the rapid expansion of the new energy vehicle market, the growing demand for cobalt has formed a sharp contradiction with the limited supply of resources. At the same time, the continued rise in cobalt prices has further aggravated the cost pressure of cathode materials, posing a huge challenge to cost control in the battery industry. Faced with the scarcity and cost issues of cobalt resources, reducing or even completely removing the cobalt content in batteries has become an important trend in battery technology innovation. The research and development of cobalt-free batteries has emerged as the times require, and is seen as a hope for solving the current dilemma. However, the decobalting of cathode materials is not an easy task, especially in solving key technical problems such as lithium-nickel mixed arrangement and metal segregation. If these problems cannot be effectively solved, they will have a serious impact on the stability, cycle life and rate performance of cathode materials. At present, the industry generally adopts the method of doping and coating other elements to make up for the lack of cobalt, so as to optimize its performance while maintaining the structural stability of the cathode material. This strategy occupies an important position in the research and development of cobalt-free batteries. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of irreversible loss of initial capacity, poor rate performance, rapid capacity decay, etc. of layered cobalt-free lithium-rich manganese-based positive electrode materials, and to provide a method for preparing a scalable Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material with simple process. No multi-step reaction is required. Li2CO3, Mn oxide, Ni oxide, Mg compound, and Al compound are fully mixed by mechanical ball milling to obtain a uniform mixed powder, and then dried and calcined to obtain the Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material. The positive electrode material has a higher specific capacity and a high voltage platform during initial charging, and has excellent electrochemical properties.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material, the method comprising:

[0008] Step 1: Add excess Li2CO3, Mn oxide, Ni oxide, Mg compound, and Al compound into a ball mill containing an organic solvent, and obtain a uniform mixed powder after being fully mixed by mechanical ball milling;

[0009] Step 2: Dry the mixed powder at 80°C for 3-10 hours;

[0010] Step 3: The obtained dry powder is mixed evenly again, and the calcination temperature is increased from room temperature to 350-500°C, and the insulation time is 3-6h. The second stage calcination temperature is 700-900°C, and the calcination time is 10-20h, so as to obtain Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material.

[0011] Furthermore, in step 1, the Mn oxide is at least one of MnO, Mn2O3, and Mn3O4; the Mg compound and the Al compound are at least one of the oxides, carbonates, and hydroxides of Mg and Al.

[0012] Furthermore, in step 1, the molar ratio of each element is Li:Mn:Ni:Mg:Al=1.2-1.26:0.6:0.2:0.001-0.01:0.001-0.01.

[0013] Furthermore, in step 1, the organic solvent is ethanol.

[0014] Furthermore, in step 2, the drying time is 5-6 hours.

[0015] Furthermore, in step three, the heating rate is 3°C / min.

[0016] The beneficial effects of the present invention compared to the prior art are:

[0017] (1) The morphology of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based cathode material prepared by a high-temperature solid phase method was analyzed. It was observed that the sample particles were evenly distributed and had an appropriate particle size, indicating that it may have good electrochemical properties.

[0018] (2)Al 3+ Doping can effectively improve the electrochemical performance of cobalt-free lithium-rich manganese-based cathode materials. The reason is that Al 3+ The addition of Mg introduces a transition metal layer, which may be due to the stronger Al-O bond that can strengthen the TM-O framework and play a role in regulating the local electronic structure, thereby enhancing the stability of lattice oxygen, thereby inhibiting the phase transition from the layered phase to the spinel phase during the cycle and improving the stability of the layered structure. 2+ Successful doping into the Li layer effectively inhibited the Li / Ni mixing, enhanced the stability of the lattice oxygen, improved the stability of the layered structure, and greatly improved the cycle stability. The synergistic effect of Al / Mg improved the electrochemical performance of the layered lithium-rich manganese-based material, reduced the loss of the first irreversible capacity, and improved the capacity and voltage decay of the electrode material during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1This is a SEM image of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Example 1 of the present invention.

[0020] Figure 2 This is a SEM image of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Comparative Example 1 of the present invention.

[0021] Figure 3 This is a TEM image of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Example 1 of the present invention.

[0022] Figure 4 This is a TEM image of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Comparative Example 1 of the present invention;

[0023] Figure 5 XRD diagrams of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Example 1 of the present invention and the cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Comparative Example 1;

[0024] Figure 6 The charge and discharge curves of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Example 1 of the present invention and the cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Comparative Example 1;

[0025] Figure 7 The cycle performance diagram of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high temperature solid phase method in Example 1 of the present invention and the cobalt-free lithium-rich manganese-based positive electrode material prepared by a high temperature solid phase method in Comparative Example 1;

[0026] Figure 8 This is a rate performance diagram of the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Example 1 of the present invention and the cobalt-free lithium-rich manganese-based positive electrode material prepared by a high-temperature solid phase method in Comparative Example 1. DETAILED DESCRIPTION

[0027] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0028] Example 1

[0029] (1) adding excess Li2CO3, manganese tetraoxide, nickel oxide, magnesium hydroxide, and aluminum hydroxide into a ball mill containing 40 ml of ethanol solvent at a molar ratio of Li:Mn:Ni:Mg:Al=1.26:0.6:0.2:0.009:0.001, and milling for 6 h using a planetary ball mill at a speed of 450 rap / min to obtain a uniform mixed powder after thorough mixing;

[0030] (2) Place the ball mill in an oven at 80°C and dry for 6 hours.

[0031] (3) Scrape off the powder to obtain dry powder, mix it evenly again, put it into a corundum crucible, and put it into a muffle furnace for roasting from room temperature to 500°C, the holding time is 3 hours, the second stage roasting temperature is 850°C, and the roasting time is 12 hours, thus obtaining a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material.

[0032] Comparative Example 1

[0033] (1) Excess Li2CO3, manganese tetraoxide and nickel oxide were added into a ball mill containing 40 ml of ethanol solvent according to the molar ratio of Li:Mn:Ni=(1.2-1.26):0.6:0.2, and the mixture was milled for 6 h using a planetary ball mill at a speed of 450 rap / min. After being fully mixed, a uniform mixed powder was obtained.

[0034] (2) Place the ball mill in an oven at 80°C and dry for 6 hours.

[0035] (3) Scrape off the powder to obtain dry powder, mix it evenly again, put it into a corundum crucible, and put it into a muffle furnace for roasting from room temperature to 500°C, the holding time is 3 hours, the second stage roasting temperature is 850°C, and the roasting time is 12 hours, so as to obtain Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material, which is recorded as Comparative Example 1.

[0036] Comparative Example 1 is also a compound prepared for the first time in the present invention. The only difference between its preparation steps and those of Example 1 is that it does not undergo Mg and Al co-doping. It is used as a comparative example mainly for comparison with the examples to study the effect of co-doping on the electrochemical properties of the positive electrode material.

[0037] The Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Example 1 and the cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Comparative Example 1 were observed using a scanning electron microscope (SEM). The results are as follows: Figure 1 As shown, the morphology of Example 1 and Comparative Example 1 was analyzed by SEM test, and it can be seen that both are broken without obvious difference. The particles of the sample in Example 1 are more evenly dispersed, with a moderate particle size, and show good electrochemical performance.

[0038] The Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Example 1 and the cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Comparative Example 1 were analyzed by XRD. The diffraction peaks of all samples perfectly corresponded to the α-NaFeO2 structure of the R-3m space group, and no other impurity peaks appeared, which indicated that the purity of the prepared materials was quite high. It is particularly noteworthy that the two pairs of diffraction peaks (006) / (102) and (018) / (110) showed a significant split state, which is an important sign that the material has a good layered structure. The spectrum also shows that Mg / Al has been successfully incorporated into the bulk lattice of the material and has little effect on the overall structure of the material, which shows that the sample not only has a high degree of crystallinity, but also maintains a good layered structure.

[0039] The Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Example 1 and the cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Comparative Example 1 were analyzed using high-resolution transmission electron microscopy (HRTEM) technology, and the transmission electron microscope images of the framed white rectangular area were displayed. In both samples of Example 1 and Comparative Example 1, clear and continuous lattice fringes were observed. It was observed that the lattice fringes spacing of the sample of Comparative Example 1 was 0.481nm, while the lattice fringes spacing of the sample of Example 1 was slightly increased to 0.487nm, which corresponds to the (003) crystal plane of LiMO2 or the (001) crystal plane of Li2MnO3. This change shows that the crystal plane spacing of the sample of Example 1 has increased compared with that of Comparative Example 1, which is consistent with the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Comparative Example 1. 2+ / Al 3+ The substitution effect of ions increases the lattice spacing of the material and enhances the stability of the material.

[0040] The Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material prepared by the high-temperature solid phase method in Example 1 is prepared into a positive electrode sheet and assembled into a battery. The preparation method of the positive electrode sheet is specifically as follows: the prepared Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material is used as the active material, acetylene black is selected as the conductive agent, and polyvinylidene fluoride (PVDF) is selected as the binder. They are weighed in a ratio of 8:1:1 and placed in a mortar, and evenly ground and mixed for 30 minutes, and then a certain amount of N-methylpyrrolidone (NMP) is added, and then evenly ground for 30 minutes to obtain a slurry with a certain viscosity. An automatic coating machine is used to obtain an electrode sheet with uniform thickness, and then it is placed in a vacuum drying oven and dried at 120°C overnight. Then, the dried electrode sheet is rolled three times with an automatic roller press, and then the electrode sheet is placed on a punching machine and cut into circular electrode sheets of the same size with a radius of 12 mm to obtain a positive electrode sheet.

[0041] The present invention adopts CR2025 button half-cell, and the whole process is carried out in a glove box (filled with argon gas). From top to bottom, the order is respectively negative electrode shell, nickel mesh, lithium sheet, diaphragm, electrode sheet, positive electrode shell, wherein the electrolyte is dripped on both sides of the diaphragm, the diaphragm is a polypropylene film, and the electrolyte is LiPF6 / ethylene carbonate (EC) + dimethyl carbonate (DMC) (mass ratio is 1:1). After being placed in order, the battery is sealed using a tablet press.

[0042] Use a charge and discharge tester to test the battery's cycle and rate performance, where the test voltage range is 2-4.8V; Figure 4 As shown, the button cell prepared by using the Mg / Al co-doped layered cobalt-free lithium-rich manganese-based positive electrode material of Example 1 of the present invention has an initial discharge specific capacity of 252 mAh / g at a rate of 0.1C.

[0043] Figure 5 The cycle performance diagram of the battery prepared by the layered cobalt-free lithium-rich manganese-based positive electrode material of Example 1 of the present invention and Comparative Example 1 is activated for two cycles at 0.1C and then cycled for 300 cycles at 1C. It can be clearly seen from the figure that the specific capacity and cycle retention rate of the sample in Example 1 are better than those of the sample in Comparative Example 1, that is, the discharge specific capacity at 1C reaches 195mAh / g, and after 300 cycles, the discharge specific capacity still remains at 180mAh / g, and the cycle retention rate reaches 92.3%.

[0044] Figure 6 The rate performance diagram of the battery prepared by the layered cobalt-free lithium-rich manganese-based positive electrode material of Example 1 and Comparative Example 1 of the present invention shows that the current densities are 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C, respectively. It can be clearly seen from the figure that the rate performance of the sample in Example 1 is significantly higher than that of the sample in Comparative Example 1. The specific capacity of the sample in Example 1 is higher than that of the sample in Comparative Example 1 at both low and high rates. The discharge specific capacities of the sample in Example 1 are 252mAh / g, 239mAh / g, 218mAh / g, 202mAh / g, 185mAh / g, and 141mAh / g, respectively.

[0045] The above results show that after co-doping with Mg and Al, the electrochemical performance is significantly better than that of Comparative Example 1, and the electrochemical performance of the positive electrode material is significantly improved.

Claims

1. A method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material, characterized in that: The method is: Step 1: Add excess Li2CO3, Mn oxide, Ni oxide, Mg compound, and Al compound into a ball mill containing an organic solvent, and obtain a uniform mixed powder after being fully mixed by mechanical ball milling; Step 2: Dry the mixed powder at 80°C for 3-10 hours; Step 3: The obtained dry powder is mixed evenly again, and the calcination temperature is increased from room temperature to 350-500°C, and the insulation time is 3-6h. The second stage calcination temperature is 700-900°C, and the calcination time is 10-20h, so as to obtain Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material.

2. The method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 1, the Mn oxide is at least one of MnO, Mn2O3, and Mn3O4; the Mg compound and the Al compound are at least one of the oxides, carbonates, and hydroxides of Mg and Al.

3. The method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 1, the molar ratio of each element is Li:Mn:Ni:Mg:Al=1.2-1.26:0.6:0.2:0.001-0.01:0.001-0.

01.

4. The method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 1, the organic solvent is ethanol.

5. The method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 2, the drying time is 5-6 hours.

6. The method for preparing a Mg / Al co-doped modified layered cobalt-free lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 3, the heating rate is 3°C / min.